Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
6x^2-xy-7y^2
=( - ( y + x )) ( 7y - 6x )
nha
a, \(x^2+6x-4y^2+9=\left(x+3\right)^2-4y^2\)
\(=\left(x-2y+3\right)\left(x+2y+3\right)\)
b, \(x^2-7x+xy-7y=x\left(x-7\right)+y\left(x-7\right)=\left(x+y\right)\left(x-7\right)\)
b)\(x^2-7x+xy-7y\)
\(=x^2+xy-7x-7y\)
\(=\left(x^2+xy\right)-\left(7x+7y\right)\)
\(=x\left(x+y\right)-7\left(x+y\right)\)
\(=\left(x+y\right)\left(x-7\right)\)
\(6x^2+xy-7x-2y^2+7y-5=-\left(y-2x-1\right)\left(2y+3x-5\right)\)
Trả lời:
\(6x^2+xy-7x-2y^2+7y-5=-\left(y-2x-1\right)\left(2y+3x-5\right)\)
Hok_tốt nha
1: \(=\left(x-3y\right)\left(x-y\right)-\left(x-3y\right)=\left(x-3y\right)\left(x-y-1\right)\)
4: \(=6x^2-4xy+3xy-2y^2+3x-2y\)
\(=\left(3x-2y\right)\left(2x+y\right)+3x-2y=\left(3x-2y\right)\left(2x+y+1\right)\)
1/\(x^2+x-xy-2y^2+y\)
=\(x\left(x+1-y\right)-y\left(x+2y-1\right)\)
6x^2 - xy - 7y^2 = -(y + x)(7y - 6x)
nha bạn chúc bạn học tốt
6x^2-xy-7y^2
=6x^2+6xy-7xy-7y^2
=6x(x+y)-7y(x+y)
=(6x-7y)(x+y)
HT